(3cJGH aj Gdabgs
(3ChdgG (B:s
(3Udi Gddg Ydjg hSde Yf GdJUhjQ GdMce jMd Ccdg HdG NdGa heG Chgeg cdGe GdYHGOi ef LQjGf NdGa ajg s
(3BNQgG (B:s
(3aGFOI PcQ GdEeGe GdYdGeI CHh GdaQL Hf GdLhRi QMeg Gddg Ydjg ai cJGH GdYQGjS Cf HYV WdHI GdYde NQL ef HdGOg ahGab TNUkG ai GdWQjb adeG cGf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3Gdabg GdESdGejs